Ultraviolet crosslinking low-smoke halogen-free insulating material as well as preparation method and application thereof

By using a combination of diaryliodoium salt, triaryliodoium salt and dipentaerythritol hexaacrylate in ultraviolet crosslinked polyethylene insulating material, the problem of insufficient aging resistance is solved, and the material still remains after aging Maintain high tensile strength and elongation at break.

CN119463337AActive Publication Date: 2025-02-18KINGFA SCI & TECH CO LTD

Patent Information

Application Number
CN202411732978.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

During the long-term use and aging process of existing ultraviolet irradiated crosslinked polyethylene insulating materials, the aging resistance performance is insufficient, resulting in a sharp decline in tensile strength and elongation at break.

Method used

Diaryliodonium salt and triaryliodonium salt are used as photoinitiators, combined with the specific crosslinking agent dipentaerythritol hexacrylate, crosslinking is initiated through ultraviolet light to form an efficient crosslinking network to improve the aging resistance of the material. performance.

Benefits of technology

It significantly improves the tensile strength and elongation of breaking ultraviolet cross-linked low-smoke halogen-free insulating material, and after aging of 720 hours, the tensile strength change rate and elongation rate of breaking of the material are small, and it has good Aging resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005160744240000051
    Figure BDA0005160744240000051
  • Figure BDA0005160744240000061
    Figure BDA0005160744240000061
  • Figure BDA0005160744240000071
    Figure BDA0005160744240000071
Patent Text Reader

Abstract

The invention discloses an ultraviolet crosslinking low-smoke halogen-free insulating material. The ultraviolet crosslinking low-smoke halogen-free insulating material is prepared from the following components in parts by weight: 15 to 30 parts of polyethylene, 10 to 25 parts of polyolefin elastomer, 40 to 60 parts of inorganic filling powder, 2 to 6 parts of photoinitiator and 1 to 3 parts of assistant crosslinking agent, the photoinitiator is selected from one or two of diaryl iodonium salt and triaryl iodonium salt; and the assistant crosslinking agent is dipentaerythritol hexaacrylate. The ultraviolet crosslinking low-smoke halogen-free insulating material not only has better tensile strength and elongation at break, but also has lower tensile strength change rate and elongation at break change rate after being aged for 720 hours, and has better aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of wire and cable materials, and more specifically, relates to an ultraviolet light cross-linked low-smoke halogen-free insulating material and a preparation method and application thereof. Background Art

[0002] Cross-linked cables have excellent high temperature resistance, higher long-term operating temperature and longer service life. In the existing technology, radiation cross-linking is widely used to prepare halogen-free insulating materials. The prepared halogen-free insulating materials are mainly used in household wiring, fire protection lines, etc. Because of their low smoke, halogen-free and low toxicity characteristics, their usage is increasing and gradually replacing traditional PVC materials.

[0003] At present, the cross-linking methods of cross-linked cables include electron beam irradiation and ultraviolet irradiation. Traditional halogen-free insulation materials, such as high-temperature, low-smoke, halogen-free 105-150℃ cable materials, are mainly cross-linked through electron beam irradiation. With the help of cross-linking agents such as TAIC and TMPTMA, polymers can achieve bridges between molecular chains, so that thermoplastic materials form a mesh structure and improve the heat resistance of the materials. However, this method requires the use of special irradiation equipment for irradiation after the finished cables are extruded. This type of irradiation equipment requires large investment, occupies a large area, and has potential hazards to the human body. Ultraviolet irradiation can be directly used in the process of extruding finished cables through ultraviolet irradiation equipment. After ultraviolet light, online cross-linking can be achieved, thereby realizing the preparation of cross-linked cables.

[0004] Patent publication number CN109485974A discloses a UV-irradiated cross-linked polyethylene insulation material, including 80-120 parts of polyethylene resin, 1-2 parts of benzophenone, 0.1-0.5 parts of benzoin dimethyl ether, 0.5-1.5 parts of triallyl isocyanate, 0.2-0.7 parts of trimethylolpropane triacrylate, 0.1-0.3 parts of UV absorber, 0.5-1.5 parts of antioxidant, and 0.5-1 parts of lubricant, which has a good cross-linking effect. However, cross-linked cables are commonly used in places where long-term power supply is required, such as internal connecting wires of electrical appliances and home decoration wiring, and have high requirements for the aging resistance of materials. How to further improve the aging resistance of UV-irradiated cross-linked polyethylene insulation materials has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] In view of the above existing technical problems, the primary purpose of the present invention is to provide a UV-crosslinked low-smoke halogen-free insulation material. The UV-crosslinked low-smoke halogen-free insulation material not only has good tensile strength and elongation at break, but also has a small change rate of tensile strength and elongation at break after aging for 720 hours, and has good aging resistance.

[0006] The second object of the present invention is to provide a method for preparing a UV-crosslinked low-smoke halogen-free insulating material.

[0007] The third object of the present invention is to provide an application of a UV-crosslinked low-smoke halogen-free insulating material in the field of preparing wires and cables.

[0008] In order to achieve the above object, the present invention is implemented by the following technical solutions:

[0009] A UV-crosslinked low-smoke halogen-free insulating material, comprising the following components by weight: 15-30 parts of polyethylene, 10-25 parts of polyolefin elastomer, 40-60 parts of inorganic filler powder, 2-6 parts of photoinitiator, and 1-3 parts of auxiliary crosslinking agent;

[0010] The photoinitiator is selected from one or two of diaryl iodonium salts and triaryl iodonium salts;

[0011] The auxiliary cross-linking agent is dipentaerythritol hexaacrylate.

[0012] The present invention adopts diaryl iodonium salt and triaryl iodonium salt as photoinitiators, and matches them with a specific auxiliary cross-linking agent dipentaerythritol hexaacrylate. The inventors have found through research that the combination of the above-mentioned photoinitiator and the auxiliary cross-linking agent has a higher cross-linking efficiency and will not remain in the polyethylene system after ultraviolet light initiation, thereby avoiding the situation in subsequent practical applications where the residual initiator and auxiliary cross-linking agent are further over-cross-linked due to continuous high temperature, resulting in a sharp decrease in tensile strength and elongation at break after aging.

[0013] The present invention adopts diaryl iodonium salt and triaryl iodonium salt as photoinitiators, and matches them with a specific auxiliary cross-linking agent dipentaerythritol hexaacrylate, so that the prepared ultraviolet light cross-linked low-smoke halogen-free insulating material not only has good tensile strength and elongation at break, but also the change rate of tensile strength and elongation at break of the material after aging for 720 hours is small, and the material has good aging resistance.

[0014] Specifically, the content of polyethylene in the ultraviolet light cross-linked low-smoke halogen-free insulation material is not less than 13.7%.

[0015] Specifically, the amount of polyethylene can be 17 parts, 19 parts, 21 parts, 23 parts, 25 parts, 27 parts, 29 parts, etc., or the interval range formed by any of the above values, such as 17-23 parts, 19-27 parts, etc., and the present invention is not limited thereto. Specifically, the amount of polyolefin elastomer can be 12 parts, 14 parts, 16 parts, 18 parts, 20 parts, 22 parts, 24 parts, etc., or the interval range formed by any of the above values, such as 12-18 parts, 14-22 parts, etc., and the present invention is not limited thereto. Specifically, the amount of inorganic filler powder can be 42 parts, 44 parts, 46 parts, 48 ​​parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, etc., or the interval range formed by any of the above values, such as 44-50 parts, 48-56 parts, etc., and the present invention is not limited thereto.

[0016] Preferably, the diaryliodonium salt is selected from one or more of 4,4′-diacetamidodiphenyliodonium hexafluorophosphate, 3,3′-dinitrodiphenyliodonium hexafluorophosphate, and diphenyliodonium hexafluorophosphate; and / or

[0017] The triaryl iodonium salt is selected from one or more of triphenyl sulfide hexafluorophosphate, triphenyl sulfide hexafluoroantimonate, and 4-tolyl diphenyl sulfide hexafluorophosphate.

[0018] Preferably, the D50 particle size of the inorganic filler powder is 0.1-5μm. Further preferably, the D50 particle size of the inorganic filler powder is 0.5-1.5μm. Specifically, the D50 particle size of the inorganic filler powder in the present invention can be 0.3μm, 0.7μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, etc., or an interval range formed by any of the above values, such as 1-3μm, 2-4μm, etc., and the present invention is not limited thereto. More specifically, the test method for the D50 particle size of the inorganic filler powder is: using deionized water as a dispersant, after the powder and the aqueous solution are fully dispersed by ultrasound, the particle size distribution is tested by a Malvern particle size analyzer.

[0019] Preferably, the inorganic filler powder is selected from one or more of magnesium hydroxide and aluminum hydroxide.

[0020] Preferably, the melt index of the polyethylene under the test conditions of 190°C and 2.16Kg is 0.2-6g / 10min. The test method of the polyethylene melt index is: GB-T3682-2000. More specifically, the melt index of the polyethylene under the test conditions of 190°C and 2.16Kg is 0.27-6g / 10min. More specifically, the melt index of the polyethylene can be 0.5g / 10min, 1.0g / 10min, 1.5g / 10min, 2.0g / 10min, 2.5g / 10min, 3.0g / 10min, 3.5g / 10min, 4.0g / 10min, 4.5g / 10min, 5.0g / 10min, 5.5g / 10min, etc., or the interval range formed by any of the above values, such as 1.5-3.0g / 10min, 2.0-4.0g / 10min, etc., and the present invention is not limited thereto.

[0021] Preferably, the melt index of the polyolefin elastomer under the test conditions of 190°C and 2.16Kg is 0.5-10g / 10min. Preferably, the melt index of the polyolefin elastomer under the test conditions of 190°C and 2.16Kg is 0.8-2g / 10min. The test method for the melt index of the polyolefin elastomer is: GB-T3682-2000. More specifically, the melt index of the polyolefin elastomer can be 1.5g / 10min, 3.5g / 10min, 5.5g / 10min, 7.5g / 10min, 9.5g / 10min, etc., or an interval range formed by any of the above values, such as 1.5-5.5g / 10min, 7.5-9.5g / 10min, etc., and the present invention is not limited thereto.

[0022] Preferably, the polyolefin elastomer is selected from one or more of EVA and POE.

[0023] Preferably, the UV-crosslinked low-smoke halogen-free insulating material further comprises 3-6 parts of antioxidants by weight. Specifically, the antioxidant comprises a primary antioxidant and / or a secondary antioxidant; the primary antioxidant is selected from a hindered phenol antioxidant, and the secondary antioxidant is selected from a hindered amine antioxidant or a phosphite antioxidant. The primary antioxidant includes, but is not limited to, tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol ester, β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate butyl octacarbonate, etc. The secondary antioxidant is selected from one or more of diphenylamine substituted derivatives (such as antioxidant 445), tris[2.4-di-tert-butylphenyl]phosphite, and 2,2'-thioethylene glycol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].

[0024] Furthermore, the present invention seeks to protect a method for preparing a UV-crosslinked low-smoke halogen-free insulating material, which comprises uniformly mixing the components, kneading, plasticizing and granulating to obtain the UV-crosslinked low-smoke halogen-free insulating material.

[0025] Preferably, the mixing is carried out at 100-200°C.

[0026] Furthermore, the present invention also claims protection for the use of a UV-crosslinked low-smoke halogen-free insulating material in the preparation of wires and cables. The wires and cables can be used as internal connecting wires for electrical appliances, household wiring, fire protection wires, etc.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention provides a UV-crosslinked low-smoke halogen-free insulating material, which adopts diaryl iodonium salts and triaryl iodonium salts as photoinitiators and is matched with a specific auxiliary crosslinking agent dipentaerythritol hexaacrylate, so that the prepared UV-crosslinked low-smoke halogen-free insulating material not only has good tensile strength and elongation at break, but also has small change rates of tensile strength and elongation at break after aging for 720 hours, and has good aging resistance. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with the specification and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0030] The raw materials of the embodiments and comparative examples are as follows:

[0031] Polyethylene 1: The melt index is 6 g / 10 min at 190 °C and 2.16 kg, LLDPE 0630H, Sinopec;

[0032] Polyethylene 2: Melt index is 0.27 g / 10 min at 190 °C and 2.16 kg, ENABLE2203MC, ExxonMobil;

[0033] Polyolefin elastomer: POE, melt index 1g / 10min at 190°C and 2.16Kg, POE 5017, Wanhua Chemical;

[0034] Inorganic filler powder: aluminum hydroxide, D50 particle size 1.2μm, OL-104LEO, Huber;

[0035] Photoinitiator 1: diphenyliodonium hexafluorophosphate, Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0036] Photoinitiator 2: triphenylsulfide hexafluoroantimonate, Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0037] Photoinitiator 3: benzophenone, Dongguan Hengqiao;

[0038] Co-crosslinking agent 1: dipentaerythritol hexaacrylate, DPHA, Miwon;

[0039] Cross-linking agent 2: trimethylolpropane acrylate, TMPTA, Dongguan Hengqiao;

[0040] Antioxidant, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, antioxidant 1010, commercially available.

[0041] Unless otherwise specified, the components (such as antioxidants) used in the parallel examples and comparative examples are all the same commercially available products.

[0042] Example 1

[0043] The weight parts of the raw materials used in Example 1 are shown in Table 1.

[0044] A UV-crosslinked low-smoke halogen-free insulation material, comprising the following specific steps:

[0045] Polyethylene, polyolefin elastomer, inorganic filler powder, antioxidant, photoinitiator and cross-linking agent are uniformly mixed, kneaded by a reciprocating machine at 170°C, plasticized and granulated to obtain ultraviolet cross-linked low-smoke halogen-free insulation material.

[0046] Example 2-Example 9

[0047] The weight parts of the raw materials used in the following examples are shown in Table 1.

[0048] The specific preparation steps of the following examples are the same as those of Example 1.

[0049] Comparative Example 1-Comparative Example 5

[0050] The weight parts of the raw materials used in the following comparative examples are shown in Table 2.

[0051] The specific preparation steps of other comparative examples are the same as those of Example 1.

[0052] Table 1

[0053]

[0054] Table 2 shows the formula components of each comparative example:

[0055] Table 2

[0056] Components Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Polyethylene 1 15 15 15 15 15 Polyolefin elastomer 20 20 20 20 20 Inorganic filler powder 55 55 55 55 55 Photoinitiator 1 / / 8 2 2 Photoinitiator 3 2 4 / / / Crosslinking agent 1 1 1 1 / 5 Crosslinking agent 2 / / / 1 / Antioxidants 4 4 4 4 4

[0057] The UV-crosslinked low-smoke halogen-free insulating materials prepared in the above-mentioned embodiments and comparative examples were crosslinked by UV irradiation (irradiation power was set at 60% to 100%), and then tested by the following method.

[0058] (1) Tensile strength and elongation at break: The tensile strength and elongation at break of UV-crosslinked low-smoke halogen-free insulation materials before and after high-temperature aging were tested according to standard GB / T 1040.3-2006, using a 5-type dumbbell specimen with h = 1 mm and L3 = 115 mm.

[0059] (2) Artificial weathering test: The test was performed according to cycle 4 in the ISO4892-2 2013 test standard, with an irradiance of 0.51 W / m 2 *nm.

[0060] (3) Elongation performance test method: Tested in accordance with GB / T 2951.21-2008 standard. Among them, the thermal elongation ≤ 175% meets the requirements.

[0061] Table 3

[0062]

[0063] Table 4

[0064]

[0065] As can be seen from Table 3 above, the UV-crosslinked low-smoke halogen-free insulation material prepared by the present invention not only has good thermal elongation, initial tensile strength and elongation at break, but also can maintain excellent tensile strength and elongation at break after 720 hours of artificial weathering. More specifically, the initial tensile strength of the prepared UV-crosslinked low-smoke halogen-free insulation material is ≥14.5MPa, and the initial elongation at break is ≥237%; after 720 hours of artificial weathering, the change rate of tensile strength is ≤25%, and the change rate of elongation at break (absolute value) is ≤26%.

[0066] It can be seen from Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 4 that the technical effect of the present invention can be achieved only when diaryl iodonium salts, triaryl iodonium salts and the auxiliary crosslinking agent dipentaerythritol hexaacrylate are used in combination. When conventional photoinitiators (such as benzophenone) or conventional auxiliary crosslinking agents (trimethylolpropane acrylate) in the art are used, the change rate of tensile strength and the change rate of elongation at break (absolute value) are large, indicating that the aging resistance is poor and it is difficult to achieve the technical effect of the present invention.

[0067] It can be seen from Example 1, Comparative Example 3 and Comparative Example 5 that when there are more photoinitiators or cross-linking aids in the system, they are likely to remain in the UV-cross-linked low-smoke halogen-free insulating material, and further cross-link during the subsequent aging process, resulting in a large change rate of tensile strength and elongation at break (absolute value) and poor aging resistance.

[0068] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to require the widest possible range that can be imagined, and the embodiments presented herein are demonstrated by the applicant's actual test results. Therefore, the applicant's intention is that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges therein, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.

Claims

1. A UV-crosslinked low-smoke halogen-free insulating material, characterized in that: The composition comprises the following components by weight: 15-30 parts of polyethylene, 10-25 parts of polyolefin elastomer, 40-60 parts of inorganic filler powder, 2-6 parts of photoinitiator, and 1-3 parts of auxiliary cross-linking agent; The photoinitiator is selected from one or two of diaryl iodonium salts and triaryl iodonium salts; The auxiliary cross-linking agent is dipentaerythritol hexaacrylate.

2. The ultraviolet light cross-linked low-smoke halogen-free insulation material according to claim 1, characterized in that: The diaryl iodonium salt is selected from one or more of 4,4′-diacetamido diphenyl iodonium hexafluorophosphate, 3,3′-dinitro diphenyl iodonium hexafluorophosphate, and diphenyl iodonium hexafluorophosphate; and / or The triaryl iodonium salt is selected from one or more of triphenyl sulfide hexafluorophosphate, triphenyl sulfide hexafluoroantimonate, and 4-tolyl diphenyl sulfide hexafluorophosphate.

3. The ultraviolet light cross-linked low-smoke halogen-free insulating material according to claim 1, characterized in that: The D50 particle size of the inorganic filler powder is 0.1-5 μm.

4. The ultraviolet light cross-linked low-smoke halogen-free insulation material according to claim 1, characterized in that: The inorganic filler powder is selected from one or both of magnesium hydroxide and aluminum hydroxide.

5. The ultraviolet light cross-linked low-smoke halogen-free insulation material according to claim 1, characterized in that: The polyethylene has a melt index of 0.2-6 g / 10 min under the test conditions of 190° C. and 2.16 kg.

6. The ultraviolet light cross-linked low-smoke halogen-free insulation material according to claim 1, characterized in that: The polyolefin elastomer has a melt index of 0.5-10 g / 10 min under the test conditions of 190° C. and 2.16 kg.

7. The ultraviolet light cross-linked low-smoke halogen-free insulation material according to claim 1, characterized in that: The polyolefin elastomer is selected from one or two of EVA and POE.

8. The ultraviolet light cross-linked low-smoke halogen-free insulation material according to claim 1, characterized in that: Calculated by weight, the invention also includes 3-6 parts of antioxidant.

9. The method for preparing the ultraviolet cross-linked low-smoke halogen-free insulating material according to any one of claims 1 to 8, characterized in that: The components are mixed uniformly, kneaded, plasticized and granulated to obtain an ultraviolet light cross-linked low-smoke halogen-free insulation material.

10. Use of the ultraviolet light cross-linked low-smoke halogen-free insulating material according to any one of claims 1 to 8 in the preparation of wires and cables.

Citation Information

Patent Citations

  • Ultraviolet irradiation cross-linked polyethylene insulating material

    CN109485974A

  • Ultraviolet-light deeply cross-linked halogen-free flame-retardant polyolefin cable material and method for preparing ultraviolet-light deeply cross-linked halogen-free flame-retardant polyolefin cable insulating or sheathing layer from same

    CN102153802A

  • Ultraviolet crosslinking low-smoke halogen-free flame-retardant polyolefin insulating material and preparation method thereof

    CN103435901A

  • Ultraviolet cross-linking oil-resistant low-smoke halogen-free flame retardant polyolefin cable material and preparation method thereof

    CN104403190A

  • LED ultraviolet cross-linked colored polyethylene cable material and preparation method thereof

    CN110938254A

Cited By

  • Irradiation cross-linked polyolefin insulating material as well as preparation method and application thereof

    CN121930575A